Faktor-Faktor Yang Berhubungan Dengan Stigma Masyarakat Terhadap Penderita HIV AIDS di Desa Kamal Kecamatan Kairatu Barat Kabupaten Seram Bagian Barat - Iin A Tukan; Windarti Rumaolat; Yerry Soumokil (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Introduction: Human immunodeficiency virus (HIV) can be transmitted sexually, through blood transfusions, sharing needles, and from mother to child during birth and breastfeeding. HIV/AIDS is a disease known in society as a curse for immoral behavior. Objective: In this study, to find out whether there is a relationship between factors and public stigma towards HIV/AIDS sufferers. Method: The type of research used in this research is descriptive correlation with a cross-sectional research approach. The sample in this research was 104 people. The sampling technique in this research is purposive sampling using the Chi-Square test. Results: based on the results of the Chi-square test, it shows that the significant p-value = 0.000 (<0.05). This means that H0 is rejected and Ha is accepted. Conclusion: there is a relationship between age, knowledge, level of education and environment and community stigma towards HIV/AIDS sufferers.